2003
DOI: 10.1046/j.1523-1747.2003.12113.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Evidence for a Novel Human Desmosomal Cadherin, Desmoglein 4

Abstract: Desmosomes are essential adhesion structures in most epithelia that link the intermediate filament network of one cell to its neighbor, thereby forming a strong bond. The molecular components of desmosomes belong to the cadherin superfamily, the plakin family, and the armadillo repeat protein family. The desmosomal cadherins are calcium-dependent transmembrane adhesion molecules and comprise the desmogleins and desmocollins. To date, three human desmoglein isoforms have been characterized, namely desmogleins 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 83 publications
0
70
0
Order By: Relevance
“…Whereas PKP1-3, PG, and DSP mapped to chromosomes 1, 12, 11, 17, and 6, respectively, all of the desmosomal cadherins were found in tandem on chromosome 18 at locus 18q12.1 (Wang et al, 1994;Simrak et al, 1995;Cowley et al, 1997aCowley et al, , 1997bBonne et al, 1998;Arnemann et al, 1991;Whittock & Bower, 2003). The curious arrangement of cadherin genes on chromosome 18 is grouped by cadherin type.…”
Section: Identification Of Genes Encoding Desmosomal Componentsmentioning
confidence: 99%
“…Whereas PKP1-3, PG, and DSP mapped to chromosomes 1, 12, 11, 17, and 6, respectively, all of the desmosomal cadherins were found in tandem on chromosome 18 at locus 18q12.1 (Wang et al, 1994;Simrak et al, 1995;Cowley et al, 1997aCowley et al, , 1997bBonne et al, 1998;Arnemann et al, 1991;Whittock & Bower, 2003). The curious arrangement of cadherin genes on chromosome 18 is grouped by cadherin type.…”
Section: Identification Of Genes Encoding Desmosomal Componentsmentioning
confidence: 99%
“…Among the desmosomal cadherins, desmoglein 2 and desmocollin 2 are the only proteins that are expressed ubiquitously in all desmosome-containing cells and tissues (Schä fer et al, 1994;Nuber et al, 1995), whereas the others have a unique tissue distribution. For example, desmoglein 4 expression was highest in the testis (Whittock and Bower, 2003), but little is known about its functional significance in spermatogenesis and fertility. It is noteworthy that both desmoglein-and desmocollin-specific peptides were needed to perturb desmosomal adhesion (Tselepis et al, 1998), illustrating that desmosomal cadherins favor heterotypic interactions to facilitate cell adhesion.…”
Section: B Cell-cell Intermediate Filament-based Desmosome Junctionsmentioning
confidence: 99%
“…Until recently, 3 human and mouse desmogleins had been characterized, namely, Dsg1, Dsg2, and Dsg3, which are expressed in tissue-and differentiation-specific manners. Recent detailed genomic analyses identified a fourth member of the desmoglein family, Dsg4, in humans and mice (7,8). It has been elegantly demonstrated that mutations in the DSG4 gene cause inherited localized hypotrichosis in humans and the lanceolate hair phenotype in mice (7).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, anti-Dsg1 IgG autoantibodies alone are necessary and sufficient for blister formation in PF, and the Dsg4/ Dsg1-cross-reacting IgG autoantibodies play only a minor pathogenic role in blister formation in pemphigus. When the amino acid sequences of the desmoglein isoforms were compared, the overall protein identity of hDsg4 was higher with Dsg3 (50%) than with Dsg1 (41%) (8).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation